Pengaruh Video Animasi tehadap Pengenalan Kosakata Bahasa Inggris di Taman Kanak Kanak Assyofa - Ashaabulmaymanah, Wafa; Muryanti, Elise (Darul Yasin Al Sys, 2024)
This research was motivated by the lack of development in children's ability to recognize English vocabulary. Teachers usually explain the material by giving examples of assignments, then the children are asked to do the assignments on the Children's Worksheet. This shows a lack of teacher professionalism in developing and introducing English vocabulary to children. This research aims to determine the effect of using animated video learning media on children's introduction of English vocabulary at Assyofa. Kindergarten. with a sampling technique in the form of cluster sampling involving classes B1 and B2, each consisting of 15 children. Data collection was carried out using a test containing 4 statements, and data analysis included normality tests, homogeneity tests, and hypothesis tests. The data collection tool used was a statement sheet, and the data was processed using the SPSS version 30 for Windows application. Data analysis shows that the average pre-test score for the experimental class is 112 and the post-test score is 218. The average pre-test result for the control class is 83 and the post-test result for the control class is 174. The final data set is homogeneous and distributed regularly. Based on the results of the hypothesis test, the sig (2-tailed) value is 0.000 <0.05. So Ha is accepted and Ho is rejected. Sho it can be concluded that there is an influence of animated videos on children's introduction of English vocabulary.